Involvement of a cinnamyl alcohol dehydrogenase of Quercus suber in the defence response to infection by Phytophthora cinnamomi - Coelho, A C; Horta, M; Neves, D; Cravador, A (Physiological and Molecular Plant Pathology, 2006)
A gene encoding a potential NADPH-dependent cinnamyl alcohol dehydrogenase (QsCAD1) (GenBank accession no: AY362455) was identiﬁed in Quercus suber (cork oak). Its complete cDNA sequence was obtained by RACE-PCR, starting from total RNA extracted from roots of seedlings of Q. suber, infected with Phytophthora cinnamomi, the causal agent of the decline and sudden death of Q. suber and Quercus ilex subsp. rotundifolia in the Iberian Peninsula. Sequence information to perform the RACE-PCR was acquired from a polymorphic fragment (C9), speciﬁcally identiﬁed by cDNA-AFLP, in leaves of epicormic shoots of a cork oak tree that suffered sudden death. RT-PCR and hybridization analysis showed that the QsCAD1 gene is up-regulated in root seedlings of Q. suber infected with P. cinnamomi. QsCAD1 has a high structural homology with VR-ERE (Vigna radiata), an enzyme that detoxiﬁes eutypine (produced by Eutypa lata, the causal agent of eutypa dieback of grapevines), to eutypinol, and with QrCAD1 (Q. ilex subsp. rotundifolia), EgCAD1 (Eucalyptus gunnii), MdCAD1 (Malus x domestica). Taken together, these results suggest that these enzymes, and namely QsCAD1 belong to a new group of CAD potentially involved in deactivation of toxins produced by phytopathogens.
Keywords: cinnamyl alcohol dehydrogenase; defence response; oak tree; phytophthora cinnamomi